In vitro and in vivo Pharmacological Activities of 14-O-Phenylpropyloxymorphone, a Potent Mixed Mu/Delta/Kappa-Opioid Receptor Agonist With Reduced Constipation in Mice - Lattanzi, Roberta; Rief, Silvia; Schmidhammer, Helmut; Negri, Lucia; Spetea, Mariana (Frontiers in Pharmacology, 2018)
Pain, particularly chronic pain, is still an unsolved medical condition. Central goals in pain control are to provide analgesia of adequate efficacy and to reduce complications associated with the currently available drugs. Opioids are the mainstay for the treatment of moderate to severe pain. However, opioid pain medications also cause detrimental side effects, thus highlighting the need of innovative and safer analgesics. Opioids mediate their actions via the activation of opioid receptors, with the mu-opioid receptor as the primary target for analgesia, but also for side effects. One long-standing focus of drug discovery is the pursuit for new opioids exhibiting a favorable dissociation between analgesia and adverse effects. In this study, we describe the in vitro and in vivo pharmacological profiles of the 14-O-phenylpropyl substituted analogue of the mu-opioid agonist 14-O-methyloxymorphone (14-OMO). The consequence of the substitution of the 14-O-methyl in 14-OMO with a 14-O-phenylpropyl group on in vitro binding and functional activity, and in vivo behavioral properties (nociception and gastrointestinal motility) was investigated. In binding studies, 14-O-phenylpropyloxymorphone (POMO) displayed very high affinity at mu-, delta- and kappa-opioid receptors (Ki values in nM, mu:delta:kappa = 0.073:0.13:0.30) in rodent brain membranes, with complete loss of mu-receptor selectivity compared to 14-OMO. In guinea-pig ileum and mouse vas deferens bioassays, POMO was a highly efficacious and full agonist, being more potent than 14-OMO. In the [35S]GTPγS binding assays with membranes from CHO cells expressing human opioid receptors, POMO was a potent mu/delta-receptor full agonist and a kappa-receptor partial agonist. In vivo, POMO was highly effective in acute thermal nociception (hot-plate test, AD50 = 0.7 nmol/kg) in mice after subcutaneous (s.c.) administration, with over 70- and 9000-fold increased potency than 14-OMO and morphine, respectively. POMO-induced antinociception is mediated through the activation of the mu-opioid receptor, and it does not involve delta- and kappa-opioid receptors. In the charcoal test, POMO produced four-fold less inhibition of the gastrointestinal transit than 14-OMO and morphine. In summary, POMO emerges as a new potent mixed mu/delta/kappa-opioid receptor agonist with reduced liability to cause constipation at antinociceptive doses.